(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study explores the mental health implication of nomadic influx and rural banditry in the north-central region of Nigeria. The persistent influx of nomadic groups, coupled with escalating rural banditry and criminality has profoundly disrupted the socio-economic fabric of the region. Through secondary sources of data collection, the research examines the distress experienced by affected populations and it effect on the Nigerian State. The findings reveal heightened levels of anxiety, depression, and post-traumatic stress disorder (PTSD) among residents, exacerbated by the frequent and unpredictable nature of attacks. Community cohesion has deteriorated, leading to a pervasive sense of insecurity and mistrust. The study underscores the necessity for comprehensive mental health interventions, enhanced security measures, and policies aimed at fostering social integration and resilience. Addressing these psychological impacts is crucial for restoring stability and promoting sustainable development in the north-central region of Nigeria